Methods for karst hazard forecast and pipeline protection in South Yakutia - Strokova L. A. Ludmila Aleksandrovna (Hydrogeology and Engineering Geology. Geoinformation Systems in Hydrogeology and Engineering Geology, 2015)
Title screen